Peran Guru Dalam Mewujudkan Pendidikan Multikultural Yang Efektif - Wulandari, Ayu; Helmi Yanti; Nurul Mubin (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
Multicultural education is becoming increasingly important in the current era of globalization, where cultural, religious and ethnic diversity has become an integral part of society. This article explores the role of teachers in realizing effective multicultural education in the classroom. Through an inclusive and diversity-sensitive approach, teachers can create a learning environment that not only respects differences, but also facilitates intercultural dialogue. This research analyzes the strategies and best practices that can be implemented by teachers to support multicultural education, as well as the challenges they may face. By understanding the vital role of teachers in this process, it is hoped that multicultural education can be implemented more effectively, producing a more tolerant and open generation.